INTEGRASI TEKNOLOGI INFORMASI DALAM PERENCANAAN PENDIDIKAN ISLAM: TANTANGAN DAN PELUANG DI ERA DIGITAL - Rastiana; M. Aditya Salam; Naila Putri Imani; Kasinyo Harto; Fitri Oviyanti (Irfani (e-Journal), 2025)
ABSTRACT In the 21st century, changes in digital technology advancement have become a global phenomenon that has an impact on many aspects including education. Digitalization not only has an impact on the way information is delivered but also on the paradigm in education fundamentally. This study uses qualitative research with a literature review approach by collecting data from various valid and relevant academic sources. The analysis technique used in qualitative literature review research is theme analysis by grouping the findings into major topics that can describe the data patterns obtained. Technological developments present challenges in the form of obstacles to infrastructure and resources, inadequate digital skills and literacy of educators, and gaps between policy formulation and technology implementation in schools. Opportunities that can be utilized are improving the standards and effectiveness of the learning process, improving the technical digital competence of teachers in the field and strategic synergy between policies and technology implementation. Several things that are recommended as strategic planning steps are the formulation and development of more inclusive and adaptive Islamic education planning, developing an open and flexible curriculum by including digital literacy, investing to improve the development of technological infrastructure in educational institutions and implementing a managerial system to carry out continuous data-based monitoring and assessment. Keywords: Islamic Education Planning, Information Technology, Digital Transformation